Adopción de las normas internacionales de información financiera (NIIF), para pymes en la empresa comercial “Crédito Fácil”, de la provincia de Cotopaxi, cantón Latacunga, parroquia Guaytacama durante el año 2022. - Sánchez Andrango, Dayana Michelle (2023)
This integrative project has the objective to Implement International Financial Reporting Standards (IFRS) for SMEs in commercial "Crédito Fácil" company in Latacunga city during 2022 year; The applied methodology is quantitative and descriptive research, with collection of pertinent information from the company to later analyze theoretical bases related to adoption of IFRS, as well as pertinent information from the company and financial statements to determine the situation, of the entity through the use of research instruments such as the interview with the accountant and the staff survey, resulting in 100%, in addition to the checklist to verify what is necessary for transition from NEC to the application of International Financial Reporting Standards 3 (IFRS 3) for SMEs in the commercial company "Crédito Fácil", for which three phases were implemented: conceptual and company diagnosis where the financial statements are analyzed vertically and horizontally, impact evaluation and planning of NEC convergence to IFRS for SMEs where the policies and those accounts that require adjustments are determined and finally the implementation of IFRS for 2023 finding a decrease of -81,534.98 in inventory due to impairment, the value adjustment of cadastral Building appraisal, having an impact on the equity of $-25,084.78.